EFFECTIVE METHODS FOR TEACHING MEDICINE VOCABULARY IN ENGLISH LANGUAGE LEARNING - Murodova Mehrangiz Umid qizi, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
In order to prepare professionals and students for successful communication in the medical area, medical vocabulary instruction is essential. Using interactive techniques, visual aids, and context-based learning, medical terminology is introduced during this process. Understanding prefixes, suffixes, and root words is crucial for deciphering complex concepts. Learners are better able to remember and use medical terminology when it is incorporated into authentic clinical situations.